Fatores de risco, proteção e resiliência em mulheres mastectomizadas acompanhadas pela Liga Feminina de Combate ao Câncer de Gurupi-TO - Marinho, Vinicius Lopes (Universidade Federal do Tocantins, 2017)
In Brazil, the breast cancer has been the major cause of deaths in female population, especially in the age between 40 and 69.The mastectomy it is the most used method aiming to remove the tumor. The procedure cause social and emotional problems and affect significantly the quality of life of the woman .the study aimed to investigate the resilience process the mastectomized women. The study have qualitative nature carried out with 10 women and the league Feminine against Câncer in Gurupi. For the collect of data was done questionnaire to characterize the participant, interview. The result of the interview was submitted to Bardin content and organized in three categories: Feelings and Experience on Diagnosis and treatment, risk factors and protective factors together with resilience process. Receiving the diagnostic of breast cancer, brought feelings like unbelief for being sick, anger, denial, guilt and fear. However, for some, the experience means learning and overcoming state. the risk factors of the survey was absent of the family and friendly support ,side effects during chemotherapy , and sadness and give up feelings sometimes together with fear during the treatment. Otherwise, the protector factors was the family support, friendships and professional support, faith in god and spirituality and the job. She understood in this study that being resilient is related to the ability to experience fears, anxieties and uncertainties, taking an active posture of coping with breast cancer, finding new meanings for the difficulties experienced and being strengthened by them.